2008
DOI: 10.1159/000164149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravenous Loop Diuretics on Outcomes of Patients Hospitalized with Acute Decompensated Heart Failure: Insights from the ADHERE Registry

Abstract: The optimal use of diuretics in decompensated heart failure remains uncertain. We analyzed data from the ADHERE registry to look at the impact of diuretic dosing. 62,866 patients receiving <160 mg and 19,674 patients ≥160 mg of furosemide were analyzed. The patients receiving the lower doses had a lower risk for in-hospital mortality, ICU stay, prolonged hospitalization, or adverse renal effects. These findings suggest that future studies should evaluate strategies for minimizing exposure to high doses of diur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
158
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(167 citation statements)
references
References 51 publications
5
158
0
4
Order By: Relevance
“…reported that diuretic resistance occurred in over one third of patients with HF and was associated with poor prognosis 9. Several studies showed that high‐dose furosemide usage was associated with poor prognosis in patients with HF regardless of an intravenous or oral administration route 9, 10, 25, 26. On the other hand, Testani et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that diuretic resistance occurred in over one third of patients with HF and was associated with poor prognosis 9. Several studies showed that high‐dose furosemide usage was associated with poor prognosis in patients with HF regardless of an intravenous or oral administration route 9, 10, 25, 26. On the other hand, Testani et al .…”
Section: Discussionmentioning
confidence: 99%
“…20 Increased risk for in-hospital mortality and renal failure have been seen with higher doses of IV loop diuretics compared with lower doses. 21 The duration of diuretic therapy may be a prognostic factor and predictor of morbidity by impacting hospital length of stay. 22 Hospital length of stay can be due to extent of congestion, but several actions exerted by parenteral diuretics may independently contribute to in-hospital complications.…”
Section: Clinical Studies In Heart Failurementioning
confidence: 99%
“…34 With increasing concerns in recent years, we have to be cognizant about liberal use of loop diuretics. 21 Loop diuretics should be used modestly, with constant dosage adjustment and with regular clinical assessment. Although literature supports several strategies for volume management, removal of excess extracellular fluid with diuretics is still the mainstay of ADHF therapy.…”
Section: Clinical Studies In Heart Failurementioning
confidence: 99%
“…1) Diuretics are usually the first-line therapy and are most frequently used for ADHF treatment, but have a possibility of worsening the renal function and prognosis of heart failure patients. [2][3][4][5] Carperitide, which is a recombinant of human atrial natriuretic peptide and produces vasodilation and natriuretic effects, is used frequently (58.2%) in Japan according to a large-scale multicenter cohort study; ATTEND registry. 6) Several reports revealed the efficacy and safety of carperitide in acute phase treatment and improvement of long-term prognosis after administration of carperitide in patients with heart failure.…”
mentioning
confidence: 99%